Acute Effects of Heel-to-Toe Drop and Speed on Running Biomechanics and Strike Pattern in Male Recreational Runners: Application of Statistical Nonparametric Mapping in Lower Limb Biomechanics - Yu, Peimin; He, Yuhuan; Gu, Yaodong; Liu, Yuwei; Xuan, Rongrong; Fernandez, Justin (Frontiers in Bioengineering and Biotechnology, 2022)
With the increased popularity of running, many studies have been conducted into footwears which are highly related to running performance and running related injuries. Previous studies investigated different shoe types as well as running shoes with different heel-to-toe drops (HTDs). However, no research was found in investigating shoes with negative values with HTD. Therefore, the aim of this study was to determine the acute effect of HTD and running speed on lower limb biomechanics and strike pattern in recreational runners. Thirteen male recreational runners wearing shoes with two different HTDs (-8mm and 8mm) performed running at three different speeds (preferred speed, 90% of preferred speed, 110% of preferred speed). Lower extremity kinematics and ground reaction forces were synchronously captured via Vicon motion analysis system and AMIT force platform. Strike index (SI), vertical average loading rate (VALR), vertical instantaneous loading rate (VILR), joint angles, excursion, eversion duration, range of motion (ROM) were calculated. Discrete values (SI, VALR, VILR, ROM, excursion eversion duration) were analyzed via two-factor repeated measures ANOVA followed by Bonferroni post hoc test for multiple comparisons. Two-factor repeated measures ANOVA in open-source factorial statistical nonparametric mapping (SnPM) was employed to analyze joint angles during entire stance phase. SI and VILR in shoes with -8mm HTD were significantly greater than those in 8mm HTD. Significant alterations of ROM occurred in the MTP, ankle and knee joints, and HTD factor primarily accounted for these changes. Joint angles (MTP, knee, and hip) during entire stance phase altered due to HTD and speed factors. Running speed primarily influenced the kinematics parameters of knee and hip joints. The results indicated that shoes with -8mm HTD may be useful to storage and return energy which was related to running performance. But according to higher VILR in -8mm HTD, it is also suggested to conduct forefoot strike gait retraining before transition from normal running shoes to running shoes with -8mm HTD.